Teknologi Big Data Untuk Keamanan Iot (Internet Of Thing) - Muhtajuddin Danny; Nurhadi Surojudin (Teknik Informatika, Universitas Pelita Bangsa, 2022)
Big data is a collection of processes from larger and wider volumes of data accurately or inaccurately and can be used to assist in an activity in a company or business. Big data is the development of a database system in general or in general. In distinguishing big data, namely the speed, volume, and type of data that can be available more and varied from the DBMS (Database Management System) in general or in general. Internet of Things or better known as IoT. This technology has driven rapid progress in various sectors. However, IoT can be an easy target for cyberattacks. The widespread adoption of IoT means that we will be familiar with finding intelligent devices connected to the Internet. This exploit threat includes network scan, remote code execution, command injection, SQL injection. Meanwhile, the threat of password attacks takes advantage of the fact that many IoT device owners do not change their default passwords. Today's IoT is also no longer only used by botnets to carry out DDoS, but also used by hackers as a source of spreading malware. Keywords : Big Data, IoT, Security, Malware